TOTAL PHENOLIC, FLAVANOID CONTENTS AND GC-MS ANALYSIS OF CANTHIUM COROMANDELICUM LEAVES EXTRACT - Sasikala, K.; CHANDRA MOHAN, S. (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: In this study methanol extract of leaves of canthium coromandelicum (Family: Rubiaceae) was screened for the presence of phytochemical components by GC-MS analysis. In addition total phenolics and flavanoids were also estimated. Methods: GC-MS analysis of plant extract was performed using a Perkin-Elmer GC Clarus 500 system and Interpretation on mass spectrum GC-MS was conducted using the database of National Institute Standard and Technology (NIST). Result: 20 chemical compounds are identified from the plant extract. Squalene (C30H50) is the major component available at RT 23.10 and 15.02% peak area. Other most prevailing phytocomponds are Phytol, 25-desacetoxy- Cucurbitacin b, n-Hexadecanoic acid, Sitosterol etc., Canthium coromandelicum contained the total phenolic of 25.49Â±0.09 mg/g and the total flavonoids of 12.37Â±0.15mg/g which are equivalent to gallic acid and quercetin, respectively. Conclusion: The presence of various bioactive compounds justifies the use of canthium coromandelicum for various ailments by traditional practitioners.